1992
DOI: 10.1111/j.1476-5381.1992.tb09091.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of BRL 38227, nitrendipine and isoprenaline on carbachol‐ and histamine‐stimulated phosphoinositide metabolism in airway smooth muscle

Abstract: LEI 9HN and *SmithKline Beecham Pharmaceuticals, Great Burgh, Epsom, Surrey KT18 5XQ1 The ability of BRL 38227 and nitrendipine to affect muscarinic agonist and histamine-stimulated [3H]-inositol phosphate accumulation in slices of bovine tracheal smooth muscle has been studied and compared with the established inhibitory effects of isoprenaline on this pathway.2 Pre-addition of BRL 38227 (5 J4M), nitrendipine (1 I1M) or isoprenaline (10 IJM) significantly inhibited the subsequent inositol phosphate response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…It has been suggested that the ability of 13-adrenoceptor agonists to inhibit Hist-stimulated [3H]-InsP accumulation arises as a consequence of the membrane hyperpolarizing action of these agents which reduce voltagesensitive Ca2"-influx in this tissue (Challiss et al, 1993). Thus in common with K+-channel openers, the inhibitory effects of ,B-adrenoceptor agonists on Hist-stimulated [3H]-InsP accumulation can be completely negated by preventing hyperpolarization (Challiss, 1992;Challiss et al, 1992). It is interesting to note that recent studies have provided evidence that whilst Salb and Iso can cause membrane hyperpolarization of guineapig trachealis and increased Rb+-efflux from bovine trachealis (Dougall et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the ability of 13-adrenoceptor agonists to inhibit Hist-stimulated [3H]-InsP accumulation arises as a consequence of the membrane hyperpolarizing action of these agents which reduce voltagesensitive Ca2"-influx in this tissue (Challiss et al, 1993). Thus in common with K+-channel openers, the inhibitory effects of ,B-adrenoceptor agonists on Hist-stimulated [3H]-InsP accumulation can be completely negated by preventing hyperpolarization (Challiss, 1992;Challiss et al, 1992). It is interesting to note that recent studies have provided evidence that whilst Salb and Iso can cause membrane hyperpolarization of guineapig trachealis and increased Rb+-efflux from bovine trachealis (Dougall et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have focused on the mechanistic actions of H 2 S in the lung-resident cells. Even though the role of K ATP channels in regulating airway functions has been reported [21; 22; 23], the effects of H 2 S on airway smooth muscle (ASM), the end-effector of acute airway narrowing, are largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…These data are inconsistent with the previous reports of inhibition of IP 3 production by K ATP channel openers in the arteries and trachea. Challiss et al [4] reported that pre-addition of lemakalim significantly inhibited the PI response to 1 µM CCh, but not to 10 µM CCh or greater, in slices of bovine tracheal smooth muscle. Since the doses of 50% effect (ED 50 ) of CCh in bovine tracheal smooth muscle is about 5.5 µM [13], the 1 µM CCh used in their study was less than the ED 50 of CCh [4].…”
Section: Discussionmentioning
confidence: 97%
“…However, since the K ATP channel seems not to be so important in airway smooth muscle, few studies, except for those of Challiss et al [4] and Kamei et al [5], have evaluated the effects of K ATP channel openers on the airway smooth muscle of bovines or dogs. These authors found that K ATP channel openers inhibited inositol phosphate or IP 3 accumulations.…”
Section: Introductionmentioning
confidence: 98%